Structural equation modeling of rural adolescent inhalant abuse across ethnic groups - Wood, James W., author; Bell, Paul, advisor; Edwards, Ruth, committee member; Chavez, Ernest, committee member; Banning, James, committee member (Colorado State University. Libraries, 2011)
This project aimed to increase understanding of inhalant abuse among ethnically diverse rural adolescents, an under-researched population when it comes to substance abuse (Pruitt, 2009). The present project used general findings about substance use from previous research reported in the literature, as well as findings specifically addressing inhalants, to test structural equation models of inhalant abuse for three major ethnic groups: African Americans, Mexican Americans and Whites. The sample consisted of survey responses from a total of approximately 17,000 rural adolescents, primarily from the Western and Southeastern United States, and was a subset of data collected under a nation-wide study of substance use by rural youth. The size and diversity of this sample allowed for the testing of Peer Cluster Theory and its ability to predict inhalant abuse across three ethnicities. The study utilized Structural Equation Modeling and included the following constructs: family caring, family sanctions, religious identification, school adjustment, peer drug associations, and inhalant abuse. According to Peer Cluster Theory, the effects of all the above factors on inhalant abuse are mediated through peer drug associations. The first hypothesis of this study was that Peer Cluster Theory would be successful as a predictive model for inhalant abuse, as it has been for other types of drug abuse (Breitmayer et al., 1993; Oetting, Donnermeyer, & Deffenbacher, 1998; Oetting, Donnermeyer, Trimble, & Beauvais, 1998). The second hypothesis, more exploratory in nature, was based on prior qualitative work (Wood et al., under review) and stated that there would be differences in model fit and/or specific regression coefficient paths across ethnic groups. The third hypothesis, based on findings reported in the literature by Mackesy-Amiti and Fendrich (2000), was that African Americans would have a lower regression coefficient for the path from school adjustment to peer drug associations than would Mexican Americans or Whites. Findings indicated that Peer Cluster Theory was validated as a predictive model of inhalant abuse for all three ethnicities. Measurement variance made ethnic comparisons tenuous, but a substantive difference was found in the regression coefficients for the path from family sanctions to peer drug associations comparing ethnicities, with higher values for African Americans than for Whites. The hypothesis that the path from school adjustment to peer drug associations would be weaker for African Americans was not supported. Implications of the findings, limitations of the study, and directions for future research are discussed.
Keywords: inhalant